Pengaruh Harga, Promosi, dan Kualitas Produk terhadap Kepuasan Konsumen AMDK Le Minerale Kabupaten Tabanan Bali pada Era New Normal - Kadek Dita Pramana Putra; Christina Heti Tri Rahmawati (LPPM Universitas Putera Batam, 2022)
This research aims (1) to find out how the price, promotion and product quality influences consumer satisfaction of Le Minerale bottled water Tabanan Bali in the new normal era, (2) to find out how the prices influences consumer satisfaction of Le Minerale bottled water Tabanan Bali in the new normal era, (3) to find out how the promotions influences consumer satisfaction of Le Minerale bottled water Tabanan Bali in the new normal era, and (4) to find out how the product qualities influences consumer satisfaction of Le Minerale bottled water Tabanan Bali in the new normal era. The population used in this study were people in Tabanan Regency who had consumed Le Minerale bottled water products at least 3 times. Sampling technique used is purposive sampling. The number of respondents is at least 100. Data collection techniques using a questionnaire. The data analysis using Microsoft Excel 2019 and SPSS version 25 program. From this research show that (1) price, promotion and product quality influences simultaneously consumer satisfaction of Le Minerale bottled Tabanan Bali in the new normal era, (2) price has no influences on consumer satisfaction of Le Minerale bottled Tabanan Bali in the new normal era, (3) promotion has influences on consumer satisfaction of Le Minerale bottled Tabanan Bali in the new normal era, and (4) product quality has influences on consumer satisfaction of Le Minerale bottled Tabanan Bali in the new normal era